Relevance of KOHA ILS in Nepal in terms of satisfaction of librarians (TULSSAA Journal, 2025)
Libraries in Nepal have implemented KOHA ILS for the automation of the library functions for more than a decade. However, KOHA ILS is not being used to its full potential. The main objective of this study was to test the suitability of KOHA ILS in Nepalese libraries. The primary source of data is used to assess the usability of KOHA ILS by librarians and the library users. This study has employed non-probability purposive sampling method. A total of 45 questionnaires were distributed to the librarians of various libraries which have implemented KOHA ILS. Out of them, 41 responses were collected. It is found that the librarians were aware of features of Koha. Most of them are satisfied with the features and performance of the software. However, only few of librarians are technically efficient for the installation and customization of software. Koha is found suitable for the Nepalese libraries but trainings and awareness programs are required.